Influence of build-up structure on the output of force transducer build-up system. (May 2019) - Liang, Wei; Yang, Xiaoxiang; Yao, Jinhui; Wei, Tieping
Highlights: A build-up structure with pendulums fixed on a balanced platen was introduced. The side force and additional moment had influences on the build-up system output. Smaller side force and additional moment were generated in the build-up structure. A 60 MN build-up system of the special structure was measured and verified. Abstract: As the primary force standard in the super large force range, force transducer build-up system played an important role to calibrate the build-up force standard with a capacity over 20 MN. To enhance the accuracy of the build-up system, the influence of build-up structure on the output of the build-up system was investigated. The parasitic components, including the side force and the additional moment, in three different build-up structures were analysed, and compared by the finite element simulation. The experiments of three 300 kN build-up systems of the three structures and a 60 MN build-up system were carried out. The experiment showed that the side force and the additional moment applied to the transducer had significant influences on the output of the transducer. The larger side force and additional moment, the larger the position error and the indication error of the BUS were. The side force and the additional moment should be minimized during the build-up structure design. The pendulum used in the build-up system could significantly reduce the additional moment generating on the transducer, especially after the pendulums were fixed on the balanced platen. The special build-up structure with the pendulum fixed on a balanced platen was verified as a proper build-up structure.